Regulation of endometrial NF-κB expression in patients with PCOS undergoing total embryo freezing - Cemil Karakus; Nurettin Turktekin; Ramazan Ozyurt (Clinical and Experimental Obstetrics & Gynecology)
Background: To investigate Nuclear Factor kappa B (NF-κB) expression pattern in the endometrial samples taken on the day of egg collection in women with polycystic ovarian syndrome (PCOS)scheduled for total embryo freezing due to the risk of ovarian hyperstimulation syndrome (OHSS). Methods: Forty women with PCOS scheduled for total embryo freezing due to the risk of ovarian hyperstimulation syndrome were included in the study. Twenty-five infertile women who decided to freeze all of their embryos for any reason other than PCOS were utilized as the control group. Endometrial sampling was performed from all patients in both groups immediately following the egg collection. Five fertile women with at least two children constituted the second control group. Endometrial sampling was performed from fertile patients during the mid-luteal phase. After immunohistochemical staining of endometrial samples with NF-κB/p65, the intensity of endometrial NF-κB/p65 expression was measured utilizing the H-score method. Results: NF-κB/p65 immunoreactivity was detected in both luminal and glandular endometrial cells from all samples. The mean H-score of endometrial NF-κB/p65 expression in the PCOS group was significantly increased compared to age and Body mass index (BMI) matched control group and fertile controls. NF-κB/p65 immunoreactivity of the control and fertile groups were found to be similar. There was no statistically significant difference in the mean H-score of endometrial NF-κB/p65 expression between the control and fertile groups. A positive and significant correlation was found between H-score values of NF-κB and E2 (estradiol), endometrial thickness, total oocyte count and total follicle stimulating hormone (rFSH) dose on human chorionic gonadotropin (hCG) day. Similarly, a strong positive correlation was found between serum testosterone, insulin levels, Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) values and NF-κB values. In addition to progesterone values on hCG day, no significant correlation was found between other parameters and NF-κB. Conclusions: Increased endometrial NF-κB/p65 expression may contribute to the diminished reproductive potential of women with PCOS undergoing total embryo freezing.